The correlation between reading speed and reading comprehension - Lia Pertiwi; Iis Sujarwati (Institute of Computer Science (IOCS), 2023)
Reading is the language you need to know. Reading increases your intelligence and allows you to acquire new knowledge and understanding so that you can learn new information more easily. Reading comprehension and reading speed are two different concepts. The degree of comprehension of a pupil is influenced by their reading speed. The purpose of this study is to evaluate the connection between students at UIN Fatmawati Sukarno Bengkulu 3A's reading speed and reading comprehension. The study used a sample of 20 TBI students. Both a reading comprehension test and a reading speed test were employed in this study's data collection. A correlation analysis was done on the data. The findings of this study demonstrate the connection between students' reading comprehension and speed. The two have a 0.135 correlation coefficient. Although slight, the association is positive. This demonstrates how reading comprehension is impacted by reading speed.Reading is the language you need to know. Reading increases your intelligence and allows you to acquire new knowledge and understanding so that you can learn new information more easily. Reading comprehension and reading speed are two different concepts. The degree of comprehension of a pupil is influenced by their reading speed. The purpose of this study is to evaluate the connection between students at UIN Fatmawati Sukarno Bengkulu 3A's reading speed and reading comprehension. The study used a sample of 20 TBI students. Both a reading comprehension test and a reading speed test were employed in this study's data collection. A correlation analysis was done on the data. The findings of this study demonstrate the connection between students' reading comprehension and speed. The two have a 0.135 correlation coefficient. Although slight, the association is positive. This demonstrates how reading comprehension is impacted by reading speed.